32‐channel phased‐array receive with asymmetric birdcage transmit coil for hyperpolarized xenon‐129 lung imaging. Issue 2 (6th November 2012) - Dregely, Isabel; Ruset, Iulian C.; Wiggins, Graham; Mareyam, Azma; Mugler, John P.; Altes, Talissa A.; Meyer, Craig; Ruppert, Kai; Wald, Lawrence L.; Hersman, F. William
<x xml:space="preserve">Abstract</x> Hyperpolarized xenon‐129 has the potential to become a noninvasive contrast agent for lung MRI. In addition to its utility for imaging of ventilated airspaces, the property of xenon to dissolve in lung tissue and blood upon inhalation provides the opportunity to study gas exchange. Implementations of imaging protocols for obtaining regional parameters that exploit the dissolved phase are limited by the available signal‐to‐noise ratio, excitation homogeneity, and length of acquisition times. To address these challenges, a 32‐channel receive‐array coil complemented by an asymmetric birdcage transmit coil tuned to the hyperpolarized xenon‐129 resonance at 3 T was developed. First results of spin‐density imaging in healthy subjects and subjects with obstructive lung disease demonstrated the improvements in image quality by high‐resolution ventilation images with high signal‐to‐noise ratio. Parallel imaging performance of the phased‐array coil was demonstrated by acceleration factors up to three in 2D acquisitions and up to six in 3D acquisitions. Transmit‐field maps showed a regional variation of only 8% across the whole lung. The newly developed phased‐array receive coil with the birdcage transmit coil will lead to an improvement in existing imaging protocols, but moreover enable the development of new, functional lung imaging protocols based on the improvements in excitation homogeneity, signal‐to‐noise ratio, and acquisition speed. Magn Reson Med 70:576–583, 2013. © 2012 Wiley Periodicals, Inc.